Desmoplastic Small Round Cell Tumour (DSRCT) - A Case Report and Review of Literature (Journal of Paediatric Surgeons of Bangladesh, 2014)
Desmoplastic small round cell tumor (DSRCT) is a rare pathologic entity that most frequently affects the peritoneal cavity and presents in pediatric and adolescent boys. It often presents at an advanced stage and has a generally poor prognosis. Sometimes it may involve liver at diagnosis. We present an unusual case of DSRCT who was present with mass in lower abdomen, pain, hepatomegaly and mild ascites. This tumor is characterized by nests of small undifferentiated cells that show immunohistochemical evidence of epithelial, mesenchymal and neural differentiation. In our patient histologicaly tumor had the characteristic features of DSRCT and were composed of small round cells with hyperchromatic nuclei and scanty cytoplasm. With various difficulties in diagnosis we ultimately reached at diagnosis by open biopsy and immunohistochemistry. Now patient is on multidrug chemotherapy (modified p6 protocol). Diagnosis and management of a rare tumor needs high level of suspicion and in time intervention.DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19552